Midwives unable to overcome language barriers in prenatal care (Italian Journal of Public Health, 2012)
Background: the present study aims to explore to what extent midwives experience barriers in providing information about prenatal screening for Down syndrome to women from diverse ethnic backgrounds, and to assess their competences to overcome these barriers.Methods: midwives from 24 Dutch midwifery practices in Rotterdam completed a structured webbased questionnaire (n=57). Data were obtained on perceived ethnic-related differences and barriers in providing information on prenatal screening, preparedness to provide cultural competent care, and the use of translated materials and professional translators. A group interview was conducted to further explore the results emerging from the questionnaire (n=23).Results: almost all midwives (95%) experienced barriers in informing women from non-Western ethnic backgrounds about prenatal screening. Midwives especially felt incompetent to provide information to pregnant women that hardly speak and understand Dutch. In total 58% of the midwives reported that they never used translated information materials and 88% never used professional interpreters in providing information on prenatal screening. The main reasons for this underutilization were unawareness of the availability of translated materials and unfamiliarity with the use of professional interpreters.Conclusions: although language barriers were reported to be the main difficulty in providing cultural competent care to patients from diverse ethnic backgrounds, only a minority of the midwives used translated materials or professional interpreters. In order to enable all pregnant women to make an informed decision whether or not to participate in prenatal screening, midwives’ competences to address language barriers should be increased.
Keywords: Language barriers; Cultural competence; Prenatal screening; Professional interpreter